Evaluasi Penerapan Basis Akrual Pada Pelaporan Keuangan RSUD Tugurejo Semarang - Ulfi Eka Fatur Rohmah; Agus Hariyanto (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2021)
This study aims to explore the extent to which PP 71 of 2010 has been implemented in the accounting process at the BLUD of Tugurejo Hospital, Semarang. Associated with a change in the government accounting system from a cash basis to an accrual basis in accordance with PP 71 of 2010. The research method used is a qualitative descriptive method with the triagulai method using 2 triagulation techniques which combine data from various sources, techniques and time so that data is obtained in the form of interviews with the head of the accounting department and sub-section, as well as obtaining the financial report documents of the 2020 Tugurejo Hospital Semarang. The results of this study show that Tugurejo Semarang Hospital has implemented the Accrual Basis SAP well, which can be seen from the results of interviews such as implementation readiness, training and learning, facilities, staff understanding and education and internal control. It is hoped that even though the Accrual Base SAP has been running well, the management of the Tugurejo Semarang Hospital and the Srmarang City Government can immediately digitize applications that are still manual, especially in reporting fixed assets